On the Origins of the Context and Meaning of the Motif of Dolphin on the Ship-Shaped Oil Lamp from the Museum of Smederevo (4th Century AD) - Gavrilović, Anđela Đ. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The dolphin motif on the ship-shaped oil lamp treasured in the Museum of Smederevo (4th century AD) has complex iconography, multi-layered and complex symbolism, and a long history. This article presents and explains how its iconography and meaning were gradually formed and developed in ancient Greek and Roman art, as well as the peculiarities of its gradual transformation into a Christian symbol. It is found that the context of the appearance of the dolphin motif in art during different epochs is not a mere coincidence, but the expression of a clear intention on the part of particularly learned artists and commissioners of works of art. Since there are no written records of this motif that would explain its iconography and meaning, and since the motif itself is by nature very hermetic, and at the same time very rare, the characteristic context of the appearance of the dolphin motif in art is also a decisive parameter for analyzing its meaning and its gradual formation.